(untitled) (Revista Lusófona de Educação, 2015)
This paper explains the foundations and development of the concept of distrib- uted leadership for equity and learning (DLE), undertaken as part of the work of the European Policy Network on School Leadership. It draws from research and reviews of research into distributed leadership and work on social justice, democratic leadership and a rich conception of democracy (holistic democracy). The importance of the concept of DLE is that, unlike most other approaches to distributed leadership, it integrates values of democracy, holistic learning and social justice into its definition. This has significant practical implications. For example, where DLE is adopted as a guiding definition, it helps to ensure that issues such as inequalities in participation, exclusion, the value of collaborative learning and factors important in creating the conditions for developing democratic citizenship are less likely to be marginalised when initiating or enhancing distributed leadership. The conceptualisation of DLE is offered as a resource and guide where there is a will to make education participative, col- laborative and a more fulfilling and self-affirming experience for all. Keywords: school leadership; democracy; social justice